Fire Standards and Safety 1976
DOI: 10.1520/stp37216s
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Room Fire Test

Abstract: This paper has attempted to indicate the need for full-scale room and compartment tests at this time, indicating two possible uses of the compartment test (for approval, or for validating small-scale tests) and has discussed a few of the factors which affect the design of the tests, using the choice of ignition source as an example of the problems involved in the test design. Reference is made to the recommended practice developed by the task group of American Society for Testing and Materials Committee E-39.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The need for a standard room fire test and some aspects of its design were discussed by Benjamin in 1977 [85]. Subsequent research in North America to arrive at a standard full-scale test was conducted primarily by Fisher and coworkers at the University of California (UCB) [86] and by Lee at the National Bureau of Standards (NBS) [87].…”
Section: Historical Overviewmentioning
confidence: 99%
“…The need for a standard room fire test and some aspects of its design were discussed by Benjamin in 1977 [85]. Subsequent research in North America to arrive at a standard full-scale test was conducted primarily by Fisher and coworkers at the University of California (UCB) [86] and by Lee at the National Bureau of Standards (NBS) [87].…”
Section: Historical Overviewmentioning
confidence: 99%
“…Wilson [63] advocated the importance of time as the unifying variable in firesafety over a decade ago. More recently Benjamin [64] emphasized the importance of reporting room burn results in units of time. Williamson [65] has found that the analysis of fullscale room burns can be systematically accomplished by the use of a state transition model.…”
Section: Dimensionality Of Rating Variablesmentioning
confidence: 99%
“…First, an extensive review of the literature was undertaken [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Then, a five-step experimental program was designed to ultimately develop a validated mathematical model able to accurately describe fires extending to walls and ceilings.…”
Section: Introductionmentioning
confidence: 99%